Anna Tietze, A History of the Iziko South African National Gallery: Reflections on Art and National Identity (Historia, 2021)
Anna Tietze, a cultural historian and research associate of the Iziko South African National Gallery which is also the country’s national gallery, published the first full-length history of this gallery that dates back to 1875. A History of the Iziko South African National Gallery: Reflections on Art and National Identity, provides a fresh academic perspective on its history. As there has been no large-scale historical inquiry into Isiko, this publication definitely fills this gap.
Keywords: Anna Tietze; national gallery; art; Contemporary Art Exhibitions